Chronic high-dosage fish oil exacerbates gut–liver axis injury in alcoholic steatohepatitis in mice: the roles of endotoxin and IL-4 in Kupffer cell polarization imbalance. Issue 5 (25th July 2017) - Li, Xiao-Jun; Mu, Yun-Mei; Qin, Qiu-Fang; Zeng, Zi-Xuan; Li, Yu-Sang; Zhang, Wei Kevin; Tang, He-Bin; Tian, Gui-Hua; Shang, Hong-Cai
Graphical Abstract: Abstract: In the present study, intestinal tight junctions (TJs) and Kupffer cell polarization were investigated in an alcoholic steatohepatitis (ASH) mouse model to uncover the potential side effects of overexposure to fish oil or omega-3 fatty acids. The mice were fed ad libitum with a liquid diet containing ethanol and fish oil. In the meantime, ethanol was given every 5–7 days by gavage to simulate binge drinking. After the 7 th binge, steatosis, necrosis, inflammatory infiltration, and bridging fibrosis were observed in the liver by histological staining. After the 13 th binge, the inducers, markers and other downstream genes/proteins of the Kupffer cell M1/M2 phenotype in the liver, serum, and small intestine were analysed. The results suggested that a chronic high dosage of fish oil alone reduced the mRNA levels of most genes tested and showed a tendency to damage the intestinal zonula occludens-1 localization and reduce the number of M2 Kupffer cells. Meanwhile, the combination of fish oil and ethanol damaged the intestinal TJs, resulting in an increased endotoxin level in the liver. Gut-derived endotoxin polarized Kupffer cells to the M1 phenotype, whereas the number of cells with the M2 phenotype (markers: CD163 and CD206) was decreased. Interleukin-4 (IL-4), an M2 Kupffer cell inducer, was also decreased. Moreover, in vitro experiments showed that IL-4 reversed eicosapentaenoic acid-induced CD163 and CD206 mRNA suppression in RAW 264.7 cells. Overall, our results showed that a chronic high dosage of fish oil exacerbated gut–liver axis injury in alcoholic liver disease in mice, and endotoxin/IL-4-induced Kupffer cell polarization imbalance might play an important role in that process.